A pilot study of parent education intervention improves early childhood development among toddlers with sickle cell disease. Issue 12 (11th August 2016) - Fields, Melanie E.; Hoyt‐Drazen, Catherine; Abel, Regina; Rodeghier, Mark J.; Yarboi, Janet M.; Compas, Bruce E.; King, Allison A.
Abstract: Background: Young children with sickle cell disease (SCD) are at risk for cognitive delay. In addition to biologic risk factors associated with SCD, environmental factors contribute to cognitive dysfunction within this cohort. Methods: We completed a single‐arm, prospective cohort study. Children with SCD between the ages of 3 and 36 months and their caregivers were followed between October 2010 and December 2013. The aim was to describe the role of a home visitation model, the home environment, and socioeconomic status in the development of young children with SCD. Primary outcome measures were the Bayley Scales of Infant and Toddler Development, Third Edition (BSID‐III) and the Home Observation for Measurement of the Environment (HOME). We hypothesized that the home visitation model, Parents as Teachers ® (PAT), would encourage positive parent–child interactions and improve cognitive outcomes. Results: Thirty‐five participants had at least two PAT visits and BSID‐III assessments. Mean scores within all five subtests of the BSID‐III improved between enrollment and exit, with significant changes within cognitive ( P = 0.016) and expressive language (EL) domains ( P = 0.002). Multivariate modeling found the HOME score associated with the exit results of the cognitive domain. Conclusion: We report longitudinal results of the first home visitation program within the early childhood SCD population and show significant improvement in cognitive and EL development. Additionally, home environment was a significant predictor of cognitive development. Randomized controlled trials to test the impact of interventions targeting the home environment are warranted for this vulnerable population.